Pengaruh Penggunaan Selimut Hangat terhadap Kejadian Shivering pada Pasien dengan Spinal Anestesi - Saifudin Zukhri; Eko Nur Haryanto (Universitas Muhammadiyah Klaten, 2026)
One of the complications that often occur in postoperative patients is the occurrence of hypothermia and shivering as a mechanism for the body's compensation mechanism against the hypotheremia. The purpose of this study is to determine the effect of the use of warm blankets on the incidence of shevering with spinal anesthesia in the Operating Room of the Klaten Islamic Hospital. Research method, a type of quantitative research with a quasi experiment design. The study involved 22 samples consisting of 11 people from the intervention group and 11 people from the control group. The treatment group was given a warm blanket from a temperature of 40OC before surgery until the end of the surgery. The control group was given a cloth blanket commonly used at RSI Klaten. The occurrence of shivering was observed during surgery until the patient was transferred to a recovering room. Bivariate analysis using chi square test. The results of the study showed that most of the respondents were female (59.1%), aged 26-55 years, and had a normal body mass index (50%). Of the 22 respondents, 14 (64%) experienced shivering, 10 of which occurred in the control group, the results of p value = 0.000 (α = 0.05) can be said to have an effect on the use of warm blankets on the incidence of shevering with spinal anesthesia. In conclusion, the administration of warm blankets has been shown to be effective against shivering recovery time. Warm blanket gynecology can be used for the prevention of shivering during surgery, especially in patients at risk of aging, thinness, and prolonged surgery.